2018
DOI: 10.19080/artoaj.2018.16.555977
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Proteins and Peptides as Potential Components of Nutraceuticals from Melinjo Seed (Gnetum gnemon)

Abstract: This mini review deals with main bioactive protein or peptide identified of melinjo (Gnetum gnemon) seed, from biochemical and agromonic aspect. These bioactive protein and peptides could be employed in the food industry as an antioxidant or antihypertension agents to replace synthetic coumpounds and may be used in formulation of functional foods, nutraceuticals, and natural drugs because of their health benefit effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Several bioactive compounds are found in melinjo [3]. Siswoyo [4] revealed that melinjo seeds contain as much as 9-11% of protein, 16.4% of fat, 58% of starch, polyphenolic compounds (flavonoid and tannins), resveratrol, gnemonoside compound one of the stilbenoi groups, and antioxidant compounds that free radicals. The nutritional content of 100 g of melinjo is listed Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Several bioactive compounds are found in melinjo [3]. Siswoyo [4] revealed that melinjo seeds contain as much as 9-11% of protein, 16.4% of fat, 58% of starch, polyphenolic compounds (flavonoid and tannins), resveratrol, gnemonoside compound one of the stilbenoi groups, and antioxidant compounds that free radicals. The nutritional content of 100 g of melinjo is listed Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile flour from the dry seeds contain crude protein 19% [3]. The protein may be used as an antioxidant because of their health benefit effects [4].…”
Section: Introductionmentioning
confidence: 99%